Impedance spectroscopy data of Agx(Ge16Sb12Se72)100-x chalcogenide glasses - Deepak S. Patil; Manisha Konale; Tomas Wagner (Data in Brief, 2019)
Impedance spectroscopy is a valuable tool for the analysis of the ionic conductivity of both solid and liquid state materials. Chalcogenide glasses are well known for their high ionic conductivity nature and wide compositional flexibility. As the GeSbSe material has high glass forming ability, it is expected that the materials can be doped with a high amount of foreign element (in the present case Ag). For all of these reasons, the GeSbSe materials can be expected as a potential candidate for solid state electrolyte for ionic batteries. The ionic conductivity behavior of Agx(Ge16Sb12Se72)100-x chalcogenide glasses were studied using impedance a primary tool.In the present article, you will find the impedance data of Agx(Ge16Sb12Se72)100-x chalcogenide glass system. From the impedance data, real and imaginary parts of conductivities were extracted and plotted as a function of applied frequency. The interpretation of the current article data were given in “Percolation behavior of Ag in Ge16Sb12Se72 glassy matrix and its impact on corresponding ionic conductivity” [1]. Keywords: Impedance spectroscopy, Ionic conductivity, Random-walk model, Chalcogenide glasses